Effect of Nitrogen Fertilizer Dose and Application Timing on Yield and Nitrogen Use Efficiency of Irrigated Hybrid Rice under Semi-Arid Conditions - Djaman, K.; Mel, V.C.; Ametonou, F.Y.; El-Namaky, R.; Diallo, M.D.; Koudahe, K. (2018)
Nitrogen fertilizer is the major input in rice production and the optimum rate and application timing management assure profitability and sustainability of the production system. This study aims to investigate hybrid rice response to different nitrogen fertilizer levels and the timing of application and quantify hybrid rice nitrogen use efficiency. Field experiments were conducted during the dry and the wet seasons 2016 at the research station of Africa Rice at Ndiaye in Senegal. Six nitrogen rates (0, 60, 90, 120, 150 and 180 kg N/ha) and three hybrid rice varieties (AR031H, AR032H, AR033H) and one inbred variety (Sahel108) and two nitrogen fertilizer application timings (three split and four split) were combined within a split-split plot design. The results showed significant effect of nitrogen rate and timing on rice grain yield that varied from 4.10 to 11.58 tons/ha and most the yield components. Rice grain yield exhibited curvilinear relationship with the applied nitrogen rates during the dry season under both nitrogen application timings and a linear relationship during the wet season under three splits. Nitrogen rate of 150 kg/ha was revealed optimum with best performance achieved by the Hybrid rice AR033H. Hybrid rice genotypes achieved greater nitrogen use efficiency compared to the inbred rice Sahel108. Hence, hybrid rice genotypes, and nitrogen rate of 150 kg/ha applied in four splits could be recommended to improve rice production and food security for achieving self-sufficiency in rice as targeted by Senegal and the neighboring countries.